Agriculture-urban water transfers: a case study of Hyderabad, South-India - Celio, Mattia; Giordano, Mark (2007)
Hyderabad is one of the fastest growing cities in India. To meet its rapidly expanding water needs, it constructed and began withdrawals from the Singur reservoir, located on a tributary of the Godavari River, in 1991. Administrative rules define allocation of water from the reservoir but prioritize Hyderabad urban needs over much longer established agricultural uses. Furthermore, the agricultural sector receives less water than even these rules allow, and urban withdrawals have changed the quantity and the timing of the water, which is available to agriculture. An increase in groundwater use by farmers may have been one response to these changes, with possible implications for surface and groundwater users further downstream. While proposals have been put forth to compensate the agricultural sector in general and the farmers directly affected by reallocation, for example by improving access to wastewater for irrigation downstream from Hyderabad or by conveying wastewater for irrigation purposes downstream Singur reservoir, compensation has not been implemented to date. The Hyderabad case study clearly highlights the advantages for devising and implementing arrangements to regulate the transfer of water from agriculture to cities, allowing a move from sectoral competition for water to efficient management of a scarce resource.